Orthodox Theology's Hide-and-Seek with Postcolonialism: Mission Praxis and Missiology as a Field Study - Papathanasiu, Athanasios N. (International review of mission, 2023)
AbstractAccording to the postcolonial approach, to understand today's world one must take into account modern colonialism (late 15th to mid-20th centuries) as well as all other forms of colonialism. Orthodox theologians have only recently and on a small scale begun to use postcolonial analysis. However, Orthodox theology can contribute to the discussion and shed more light on both the historical experience and the future course of the debate. In particular, the postcolonial perspective can intersect with missionary praxis and missiology, as the Orthodox Church began to be seriously active in the missionary field (of sub-Saharan Africa and the Far East) in the 1960s, that is, at the end of the classical colonial period. Its experience confirms that colonialism entails not only direct imposition on the colonized but also the colonized people's internalizing of the colonizers’ logic. The postcolonial approach thus invites self-criticism. The obligation to be self-critical is at the heart of the Orthodox tradition, despite the fact that it is often forgotten, resulting in nightmarish distortions and neo-colonial attitudes. At the same time, the postcolonial perspective reinforces the liberating mission of the gospel and patristic theology in all human contexts. In this way, postcolonialism is called to come to a fruitful completion with anti-colonialism and to contribute to the key demand of Orthodox ecclesiology, which is the formation of authentically local churches and not branches of other, national churches.